Land use alters dominant water sources and flow paths in tropical montane catchments in East Africa - Jacobs, S.R.; Timbe, E.; Weeser, B.; Rufino, Mariana C.; Butterbach-Bahl, Klaus; Breuer, Lutz (Copernicus GmbH, 2018)
Conversion of natural forest to other land uses could lead to significant changes in catchment hydrology, but the nature of these changes has been insufficiently investigated in tropical montane catchments, especially in Africa. To address this knowledge gap, we identified stream water sources and flow paths in three tropical montane sub-catchments (27–36 km2) with different land use (natural forest, smallholder agriculture and commercial tea plantations) within a 1 021 km2 catchment in the Mau Forest Complex, Kenya. Weekly samples were collected from stream water, precipitation and soil water for 75 weeks and analysed for stable water isotopes (δ2H and δ18O) for mean transit time estimation, whereas trace element samples from stream water and potential end members were collected over a period of 55 weeks for end member mixing analysis. Stream water mean transit time was similar (~ 4 years) in the three sub-catchments, and ranged from 3.2–3.3 weeks in forest soils and 4.5–7.9 weeks in pasture soils at 15 cm depth to 10.4–10.8 weeks in pasture soils at 50 cm depth. The contribution of springs and wetlands to stream discharge increased from 18, 1 and 48 % during low flow to 22, 51 and 65 % during high flow in the natural forest, smallholder agriculture and tea plantation sub-catchments, respectively. The dominant stream water source in the tea plantation sub-catchment was spring water (56 %), while precipitation was dominant in the smallholder agriculture (59 %) and natural forest (45 %) sub-catchments. These results confirm that catchment hydrology is strongly influenced by land use, which could have serious consequences for water-related ecosystem services, such as provision of clean water.